A Mekanisme Ventilasi Pasif pada Arsitektur Vernakuler: Analisis Konstruksi Timpa Laja pada Rumah Bugis Pagata - Hariadi, Akhmad; Rahman, Akbar; Febrita, Yuswinda (Nusantara Journal of Science and Technology, 2025)
Vernacular architecture possesses climate adaptation strategies that are frequently overlooked in contemporary design. This study aims to elucidate the passive cooling mechanism of the Timpa Laja (gable roof element) in the Bugis Pagatan house. The research employs a Single Case Study method with a descriptive-analytical approach. The object of study is focused on the stilt house typology featuring a multi-tiered (two-tiered) Timpa Laja construction, representing the social stratum of community leaders. The analysis involves dissecting the timber shingle construction details and simulating airflow logic using the Stack Effect principle. The results indicate that the Timpa Laja is not merely an aesthetic status marker but functions technically as a "Breathing Wall." The overlapping timber plank construction and the presence of horizontal gaps between roof tiers create an effective dual exhaust pathway for hot air. These findings underscore that vernacular design is capable of preventing heat traps, a common issue in modern massive wall construction.